2015
DOI: 10.1259/dmfr.20140337
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measurements made on scanned cast models using the 3Shape R700 scanner

Abstract: Objectives: In dentistry, the latest technological advancements have been incorporated primarily into diagnostic tools such as virtual dental models. The aim of this study was to evaluate the reliability of measurements made on digital cast models scanned in the 3Shape R700 scanner (3Shape, Copenhagen, Denmark) that uses a non-destructive laser beam to reproduce model surfaces so that the plaster model is not destroyed. Methods: The sample consisted of 26 cast models, and 6 linear measurements were made on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…Moreover, a significant difference in terms of trueness of scans produced with the IOS and the CBCT was noticed; this difference was greater (with higher deviations) in the mandibular models than in the maxillary models. In agreement with several studies reported in the literature [ 18 , 19 , 20 , 21 , 22 , 23 ], our results confirm that the precision of OS was within an acceptable range. Even if these studies were able to prove the reliability of the OS for the digitalization of dental models, other reports have outlined its limitation in cases with improper dental alignment [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a significant difference in terms of trueness of scans produced with the IOS and the CBCT was noticed; this difference was greater (with higher deviations) in the mandibular models than in the maxillary models. In agreement with several studies reported in the literature [ 18 , 19 , 20 , 21 , 22 , 23 ], our results confirm that the precision of OS was within an acceptable range. Even if these studies were able to prove the reliability of the OS for the digitalization of dental models, other reports have outlined its limitation in cases with improper dental alignment [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study protocol was determined to qualify for exempt status according to 45 CFR 46.101(b) by the Institutional Review Board of the University of Texas Health Science Center at Houston (HSC-DB-17-0064). The scanner, which has been previously shown to be a reliable tool for creation of a digital file from a physical model, 16 was calibrated before scanning the plaster models. Each arch was scanned separately, resulting in 24 separate STL files.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements are defined previously. 17,25 significant differences in patient anxiety and stress levels during the two procedures. An explanation of the findings in the present study might be that the accompanying parents' dental anxiety or general state of anxiety had affected the child.…”
Section: Patient Experiencementioning
confidence: 97%
“…On the digital models, the 3Shape software was used to measure the distances (OrthoSystems 2015-1, Version 1.6.1.10, Patch 10). The following four distances were registered in all three settings: 17 TC3: Distance between the cusp tips of the permanent upper canines TC6: Distance between the mesiofacial cusp tips of the permanent upper first molars TC6,3þ: Distance between the mesiofacial cusp tip of the permanent upper right first molar and the cusp tip of the permanent upper right canine TCþ3,6: Distance between the mesiofacial cusp tip of the permanent upper left first molar and the cusp tip of the permanent upper left canine…”
Section: Dental Arch Distancesmentioning
confidence: 99%